Labor Market Competition and Inequality - Jose Garcia-Louzao; Alessandro Ruggieri (Center for Economic Studies and ifo Institute (CESifo), 2023)
Does competition in the labor market affect wage inequality? Standard textbook monopsony models predict that lower employer labor market power reduces wage dispersion. We test this hypothesis using Social Security data from Lithuania. We first fit a two-way fixed effects model to quantify the contribution of worker and firm heterogeneity to wage dispersion and document that the compression of dispersion in firm fixed effects has been the main source of the decline in inequality over the past 20 years. Using a theory-based relationship, we then leverage variation across sectors and over time to show that a 10 percentage point increase in labor market competition leads to a 0.7 percentage point reduction in the variance of firm-specific wage components. A counterfactual exercise using our preferred estimates suggests that the increase in labor market competition can explain at least 15 percent of the observed decline in overall wage inequality.
Keywords: J31; J42; O15; 330; wage inequality; firm heterogeneity; monopsony; labor supply elasticity